Determining the adsorption of dissolved salt from aqueous flow through a packed bed - Tarannum, Ruhania (Kansas State University, 2019)
Two radio-tracer experiments were designed and performed in the thermal hydraulics laboratory in the Mechanical and Nuclear Engineering Department at Kansas State University. The experiments were intended to reproduce the deposition of dissolved impurities in a debris bed into which salt water had been infused. NaCl and SrCl₂ salt containing radioisotopes Na-24 and Sr-85 were used as radio tracers in two experiments to study salt deposition in a tightly packed bed of alumina particles and resin mixture. Color changing cation exchange resin adsorbed the dissolved salt from the injected salt water solution by mutually exchanging corresponding cations. Radiation emitted from the radioactive salt in the bed was detected using a collimated multiple detector system of NaI(Tl) scintillation detectors. The activity and thus the mass of the deposited salt within the interrogated volumes are proportional to the detector response. A Monte Carlo N-Particle (MCNP) model was developed to study the relationship between response and activity/mass. The ultimate purpose was to estimate the build up and retention of tracer within selected regions of the debris bed. In the first radio tracer experiment, radioactive NaCl salt solution was injected into a packed bed. The gamma rays emitted from the radioactive Na-24 were detected by two NaI(Tl) detectors placed on one side of the packed bed, near the packed bed's top and bottom, respectively. In the second experiment a mixture of radioactive SrCl₂ and non-radioactive NaCl salt solution was infused into a packed bed. In this experiment four NaI(Tl) detectors were incorporated in four different locations along the height of the packed bed to detect the gammas emitted by Sr-85. In both experiments, salt solutions were injected at constant flow rate of 10ml/min using an injection pump. All the detectors were placed at the same side of the packed bed and were collimated through lead shields in the two experiments. Investigating Na-24 tracer experiment and analyzing the detector response data, it was observed that the salt particles mostly adsorbed near the upper portion of the packed bed and almost no salt particles were present in the bottom section of the packed bed. The color change pattern of the resin along the packed bed as well as the radiation counting data of the top and bottom detectors provided the strong evidence of this conclusion. The developed MCNP model resembling the actual experimental set up provided the estimate of the radioactive tracer activity and corresponding detector response. By correlating the simulation results of MCNP model for detector response with the experimental data of radiation detection in Na-24 tracer experiment, it was estimated that approximately 7.41 ± 0.21pg Na-24 was deposited at saturation.In the Sr-85 experiment, it was observed through the resin color change that the salt solution travelled almost all the way through the packed bed system. From the experiment it was estimated that 458.032 ± 18.68pg, 79.54 ± 7.68pg and 39.82 ± 5.4pg of Sr-85 were deposited locally within the packed bed in the vicinity of detector-1, detector-2, and detector-4 respectively. Little or no Sr-85 was deposited in the location of the packed bed near detector-3. It is presumed the fact that the packed bed was not formed homogeneously and possibly present a very small amount of resin in the location of packed bed near the detector-3 . It is significant that locations where there is little adsorption of salt can be clearly identified in radio-tracer studies.
Keywords: Adsorption; Packed bed; Radiotracer method; Dissolved salt adsorption